(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
The article is devoted to the naive (insite) literature – to variety of phenomena, related to the border sphere between folk and professional literature. Some of the dom-inant characteristics of this kind of texts are defined by the analogy with the character-istics of a naive fine art. The work «Stepan and Tatyana» by M. Morozik, the Belarus-ian peasant poet of the XIX – beginning of XX century, is analyzed. The author reveals the main problems of the study of naive literature in this case.